Spatial Temporal Condition of Recent Seismicity In The Northern Part of Sumatra - Inna Nurana; Andrean Vesalius Hasiholan Simanjuntak; Muksin Umar; Djati Cipto Kuncoro; Syamsidik Syamsidik; Yusran Asnawi (Elkawnie: Journal of Islamic Science and Technology, 2021)
Abstract: The condition of stress and recent seismicity in the seismic-prone area can be statistically analyzed with the Gutenberg-Richter relation (Log N = a-bM). We apply this relation to the hypocenter distribution for the period 1970-2020 with M ≥ 4 and depth ≤ 100 km in the northern part of Sumatra. Spatially, The results obtained a-values and b-values that figure a lateral heterogeneity and stress accumulation at the interface zone in the subduction system and the northern segmentation of the Seulimeum fault. In time, both zones illustrate a slow time-to-failure cycle and the seismic gap with high-stress accumulation in the specific clusters with high parameter values. The results of the spatial-temporal analysis illustrate that a low statistical parameter value usually precedes each major earthquake event.Abstrak: Kondisi stress dan seismisitas terkini di daerah rawan gempa dapat dianalisis secara statistik dengan hubungan Gutenberg-Richter (Log N = a-bM). Kami memakai hubungan ini pada distribusi hiposenter pada periode 1970 - 2020 dengan M ≥ 4 dan kedalaman ≤ 100 km di bagian utara Sumatera. Secara spasial, hasil yang diperoleh yaitu nilai-a dan nilai-b yang menggambarkan heterogenitas lateral dan akumulasi stress pada zona pertemuan di sistem subduksi dan segmentasi utara dari sesar Seulimeum. Secara waktu, kedua wilayah menggambarkan siklus time-to-failure yang lambat dan zona seismic-gap dengan akumulasi stress yang tinggi pada kluster tertentu dengan nilai parameter yang tinggi. Hasil analisis spasial temporal menggambarkan bahwa setiap kejadian gempa besar biasanya didahului dengan nilai parameter statistik yang rendah.